2005
DOI: 10.1158/0008.5472.can-04-3869
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Inhibition of Estrogen Receptor-α–Negative Mouse Mammary Tumorigenesis

Abstract: Tamoxifen reduces the relative risk of breast cancer developing from specific premalignant lesions. Many breast cancers that arise after tamoxifen treatment are estrogen receptor-alpha (ER-alpha)-negative, although premalignant lesions such as atypical ductal hyperplasia are highly ER-alpha-positive. The p53 null mouse mammary epithelial transplant model is characterized by ER-alpha-positive premalignant lesions that give rise to both ER-alpha-positive and ER-alpha-negative tumors. Given this progression from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…We found that three out of eight (37.5%) tumors were ER and PR positive (Figures 4a and b) and that such tumors were benign adenomas and/or adenocarcinomas. Loss of ER in mouse models is known to correlate with a tumor's progression to malignancy (Medina et al, 2003); we also found that aggressive areas of squamous carcinomas showed no detectable immunostaining of ER or PR, suggesting that Pak1 hyperactivation plays a role in the development of hormone independence in some mammary gland tumors (Figure 4c, d, e and f).…”
Section: Pak1 In Tumor Formation R-a Wang Et Almentioning
confidence: 62%
See 1 more Smart Citation
“…We found that three out of eight (37.5%) tumors were ER and PR positive (Figures 4a and b) and that such tumors were benign adenomas and/or adenocarcinomas. Loss of ER in mouse models is known to correlate with a tumor's progression to malignancy (Medina et al, 2003); we also found that aggressive areas of squamous carcinomas showed no detectable immunostaining of ER or PR, suggesting that Pak1 hyperactivation plays a role in the development of hormone independence in some mammary gland tumors (Figure 4c, d, e and f).…”
Section: Pak1 In Tumor Formation R-a Wang Et Almentioning
confidence: 62%
“…However, most of the mammary gland animal models are estrogen receptor (ER) and progesterone receptor (PR) negative, with the exception of the p53 mouse model (Medina et al, 2003) and the murine mammary tumor virus-Wnt1 model (Bocchinfuso et al, 1999). Therefore, we next examined the status of ER and PR in Pak1-TG-induced tumors.…”
Section: Pak1 In Tumor Formation R-a Wang Et Almentioning
confidence: 99%
“…Loss of p53 does not inhibit the expression of ER in normal mammary cells, since ER is expressed in p53-null mammary epithelia (data not shown and Medina et al, 2003). Loss of p53 does not have a significant correlation with the ER status of human breast tumors, and 20% of tumors arising in mammary epithelia from p53-knockout mice express ER (Barbareschi et al, 1996;Medina et al, 2002).…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, our proposed model, which emphasizes the significance of ER␣ signaling in the epithelium, might also suggest that tamoxifen has a direct effect on the growth of premalignant lesions in selected ER␣-positive murine mammary cancer models. Recent studies by Medina et al demonstrate that tamoxifen had a profound impact on the prevention of mammary tumorigenesis in the p53 knockout transplant model (20). The ER␣-expressing breast cancer models in combination with the ER␣ conditional knockout model will be invaluable for studying ER signaling in premalignant and cancerous lesions of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%